2014
DOI: 10.1523/jneurosci.2102-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Brain Injection of α-Synuclein Induces Multiple Proteinopathies, Gliosis, and a Neuronal Injury Marker

Abstract: Intracerebral injection of amyloidogenic ␣-synuclein (␣S) has been shown to induce ␣S pathology in the CNS of nontransgenic mice and ␣S transgenic mice, albeit with varying efficiencies. In this study, using wild-type human ␣S transgenic mice (line M20), we demonstrate that intracerebral injection of recombinant amyloidogenic or soluble ␣S induces extensive ␣S intracellular inclusion pathology that is associated with robust gliosis. Near the injection site, a significant portion of ␣S inclusions are detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
120
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(133 citation statements)
references
References 79 publications
(40 reference statements)
13
120
0
Order By: Relevance
“…M20 ␣S Tg mice were generated similarly to the M83 line with the mouse prion protein promoter driving expression, but they express wild-type human ␣S rather than human ␣S containing the A53T mutation (41). Additionally, they express similar or higher levels of human ␣S with neuroanatomical distribution similar to that of M83 mice, but they never intrinsically develop a motor impairment phenotype or ␣S inclusion pathology (37,41,49). None of the M20 ϩ/Ϫ i.p.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…M20 ␣S Tg mice were generated similarly to the M83 line with the mouse prion protein promoter driving expression, but they express wild-type human ␣S rather than human ␣S containing the A53T mutation (41). Additionally, they express similar or higher levels of human ␣S with neuroanatomical distribution similar to that of M83 mice, but they never intrinsically develop a motor impairment phenotype or ␣S inclusion pathology (37,41,49). None of the M20 ϩ/Ϫ i.p.…”
Section: Resultsmentioning
confidence: 99%
“…injection of Δ71-82 ␣S, which lacks the ability to form fibrils or seed ␣S amyloid in vitro and in cultured cells under relatively physiologic conditions (42)(43)(44)(45), is more difficult to be explained by a conformational templating mechanism. Cerebral injections of Δ71-82 ␣S were previously shown to also have the ability to induce ␣S pathology in ␣S Tg mice, although with less efficiency than ␣S fibs (36,37). However, the possibility that in vivo, a small amount of exogenous Δ71-82 ␣S might spontaneously acquire amyloidogenic properties over time cannot be excluded, since under nonphysiological conditions (i.e., the presence of SDS), it can be artificially induced to form amyloid fibrils (51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the application of The assignments are represented in percentage and were attributed to each peak observed according to Susi and Byler (75). pathological aSyn species has been reported to induce a glial response in vivo (20,36), we investigated the state of the astrocytes by probing for glial fibrillary acidic protein (GFAP). An increase in GFAP levels could only be detected in cells exposed to WT -Cu 2+ and H50Q -Cu 2+ , likely because of the development of reactive astrocytes, as GFAP staining revealed a phenotype compatible with reactive astrocytes (37) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is consistent with literature reports demonstrating that the propagation and spreading of α-Syn pathology is prominent when the injected PFFs and host-expressed monomers are from the same species. In most of these studies, seeding and spreading of α-Syn pathology was observed when mα-Syn PFFs were injected into non-Tg mice expressing mα-Syn (40)(41)(42) or when hα-Syn PFFs were injected into Tg mice expressing human α-Syn protein (43)(44)(45)(46)(47)(48)). …”
Section: Discussionmentioning
confidence: 99%